2015
DOI: 10.1186/s13395-015-0061-7
|View full text |Cite
|
Sign up to set email alerts
|

Pax3-induced expansion enables the genetic correction of dystrophic satellite cells

Abstract: BackgroundSatellite cells (SCs) are indispensable for muscle regeneration and repair; however, due to low frequency in primary muscle and loss of engraftment potential after ex vivo expansion, their use in cell therapy is currently unfeasible. To date, an alternative to this limitation has been the transplantation of SC-derived myogenic progenitor cells (MPCs), although these do not hold the same attractive properties of stem cells, such as self-renewal and long-term regenerative potential.MethodsWe develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We have found that the three factors HEYL, KLF4, and MYOD, without exogenous PAX3 also induced PAX3-GFP cells from mesodermal cells; however, PAX7 , CALCR , or NAP1L5 transcripts in GFP + cells without exogenous PAX3 were all decreased and showed less myogenic differentiation in vitro . Furthermore, additional expression of PAX3/PAX7 is probably important for the long-term maintenance of MuSCs (Buckingham and Relaix, 2015), and the activation of transient PAX3 promotes ex vivo expansion of mouse PAX7-positive MuSCs (Filareto et al., 2015). Manipulation of culture medium by itself, without the introduction of expression vectors, is being used to promote the formation of myogenic cells for cell therapy (Chal et al., 2015), although the addition of the four factors that we describe increased the production of MuSCs and also conferred more adult MuSC-like properties as discussed.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that the three factors HEYL, KLF4, and MYOD, without exogenous PAX3 also induced PAX3-GFP cells from mesodermal cells; however, PAX7 , CALCR , or NAP1L5 transcripts in GFP + cells without exogenous PAX3 were all decreased and showed less myogenic differentiation in vitro . Furthermore, additional expression of PAX3/PAX7 is probably important for the long-term maintenance of MuSCs (Buckingham and Relaix, 2015), and the activation of transient PAX3 promotes ex vivo expansion of mouse PAX7-positive MuSCs (Filareto et al., 2015). Manipulation of culture medium by itself, without the introduction of expression vectors, is being used to promote the formation of myogenic cells for cell therapy (Chal et al., 2015), although the addition of the four factors that we describe increased the production of MuSCs and also conferred more adult MuSC-like properties as discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Both Pax3-and Pax7-reprogrammed mouse progenitors were shown to engraft when transplanted in a mouse model. Pax3-or Pax7-reprogrammed hPSCs can generate myogenic progenitors that are CD29 (ITGβ1) + /CD44 + / CD56 + and CXCR4 − /CD106 (VCAM1) − and which can engraft into mouse muscle (Darabi et al, 2012;Filareto et al, 2015) (Box 1). Overexpression of Mesp1 has also been used to produce putative cardio-pharyngeal progenitors with the capacity to differentiate into both cardiac and cranial paraxial mesoderms (Chan et al, 2013;Lescroart et al, 2014).…”
Section: Direct Reprogramming Strategies Using Transcription Factorsmentioning
confidence: 99%
“…5A), but no change in satellite marker Myf5 (Relaix et al . 2006, Young & Wagers 2010, Filareto et al . 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that although the increased expression of MyoD1 and Pax3 may drive the proliferation and differentiation of progenitor cells (Relaix et al . 2006, Young & Wagers 2010, Filareto et al . 2015), increased expression of Ifnγ may inhibit myogenin activity and prevent differentiation (Londhe & Davie 2011).…”
Section: Resultsmentioning
confidence: 99%